Perancangan Sistem Informasi Pelaporan Morbiditas Rawat Inap Guna Menunjang Kualitas Mutu Pelayanan - Yulista, Yulista; Abdussalaam, Falaah; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The development of technology can help the efficiency of the hospital staff, especially in the advertising of medical care services, such as making a morbidity report in the hospital. I Found some problems in the medical record installation, that is, the processing of the morbility reports and incomplete registration of patient records carried out by nurses until the quality of the reporting decreased and was not urgent. Therefore, an information system is needed to streamline the performance of recording officers in making complete, fast and accurate morbidity reports for inpatients. Metode is used to gather investigative data that includes observations, interviews and library studies with descriptive analysis. Metode system development means the method of extrleme programming. The results of the inflamation system with the use of the methods chosen are able to improve the effectiveness of the officer in the preparation of the morbidity report of the inpatient patient until the reporting is carried out by the medical records officer to disclose the accurate data. That way, this information system will maximize the service of patients as long as the quality of hospital services can be improved.